Sustainable Tourism and Historical Heritage: Integrating Ancient Practices with Contemporary Tourism in the Context of Mahakumbh for a Viksit Bharat - Ankita Srivastava, (AG Volumes, 2026)
Mahakumbh Mela is the expression of India’s rich traditional, cultural, religious and spiritual identity. Mahakumbh is celebrated once in every twelve year in Prayagraj Uttar Pradesh, where millions of pilgrims gather to the transcendental experience and take a dip in holy Triveni Sangam. Such mega events have the potential to be a sustainable model for the spiritual and inclusive sustainable tourism which blends the ancient cultural values with contemporary sustainable concerns. The present study is based on the secondary sources, user generated content available on various social media platforms, media coverage of the event, local people experience and observations. The observation method had the logistical constraints so the study largely relies upon the user generated content. The study critically evaluates the integration between community engagement, technological interventions and eco-friendly infrastructure set up. The findings of the study show the Mahakumbh model as an example of sustainable and inclusive framework for managing such mega events. MahaKumbha serve as an example of inclusive and sustainable tourism blending the traditional values with modern governance tools. The study concludes with a recommendation framework emphasizing community empowerment, digital narratives and the execution of this model in other pilgrimage sites in accordance with the vision of Viksit Bharat.